Action Against Assistance in the Abuse of Residence Permits for Foreign Nationals by the Class I Immigration Office TPI Tanjung Perak (Case Study of the Surabaya District Court Decision No. 4485/Pid.C/2021/PN Sby) - Frans Xaverius Ulu; Andy Usmina Wijaya (Journal of Law, Politic and Humanities, 2025)
Indonesia is a unitary state that has a very large territory so that state sovereignty is a non-negotiable price that must be maintained. Indonesia has the right to the authority to regulate its own order in protecting its territory including in terms of granting residence permits to foreigners who enter and settle in its territory. Because it is very possible for foreigners to misuse residence permits, where this violation usually also involves Indonesian citizens to take advantage for personal gain unlawfully. The purpose of this writing is to find out and analyze the actions of the Immigration Office in taking action against foreigners who violate their residence permits in Indonesia, especially in the area of the Class I Tanjung Perak Surabaya Immigration Office. The method used in this writing is a normative literature study, namely based on documents obtained from various sources related to the main problem.